Association of family structure with type 1 diabetes management and outcomes in adolescents: A population‐based cross‐sectional survey. Issue 3 (29th December 2020) - Baechle, Christina; Stahl‐Pehe, Anna; Castillo, Katty; Selinski, Silvia; Holl, Reinhard W; Rosenbauer, Joachim
Abstract: Background: Diabetes therapies have enormously changed during past decades, but only few studies have analyzed the association between family structure and diabetes management and outcomes. Objective: To analyze cross‐sectionally the associations of family structure with type 1 diabetes (T1D) management and various diabetes outcomes. Methods: A total of 1635 11‐ to 17‐year‐old participants and their parents completed one of three baseline surveys as part of a nationwide, population‐based cohort study on early‐onset, long‐standing T1D. Associations between family structure and outcome variables were analyzed by multivariable linear/logistic regression. Results: Compared to adolescents living with both parents (reference), HbA1c was 0.48% (95% confidence interval 0.24; 0.71) / 5.2 (2.6; 7.8) mmol/mol higher in adolescents living with one parent and 0.34% (0.08; 0.59) / 3.7 (0.9; 6.5) mmol/mol higher in those living with one parent and her/his partner. The blood glucose self‐monitoring (SMBG) frequency was lower (single parent: −0.6 (−1.1; −0.2), parent and partner:‐0.5 (−1.0; 0.0)) and parents reported more long‐term consequences related to school or work (ORsingle‐parent 1.52 (0.90; 2.57), ORparent + partner 1.50 (0.86; 2.60)). While living with one parent was associated with increased odds of insulin injection vs. insulin pump therapy (OR 1.61 [1.13; 2.29]), the odds of low hypoglycemia awareness (OR 1.75 [1.00; 3.08]) and diabetes complications (1.32 [0.78; 2.22]) were higher in people living with a parent and her/his partner. Conclusions: Living with only one parent with or without a new partner was associated with less SMBG and pump use and poor diabetes outcomes. Future studies to explore the underlying mechanisms are required.